PENGARUH MARKETING ACTIVITY TERHADAP RETURN ON ASSET DAN MARKET TO BOOK VALUE PERUSAHAAN DI SEKTOR INDUSTRI KEUANGAN NON-BANK - Ciawi Aaron (Business Accounting Review, 2015)
This study aimed to examine the effect of marketing activity to return on asset (ROA) and market to book value (MTBV). Marketing expense represented the marketing activity; while company size, and company age were control variables to explain the relationship of marketing activities on profitability and market value. Data used in this study were secondary data from the company's annual report. This study used 35 companies in the sector of non-bank financial industry which is listed in Indonesian Stock Exchange from 2008 to 2013 by using purposive sampling method. Hypotheses in the study analysed by using multiple regression method. The result showed that marketing activities had influence on MTBV but had no influence on ROA. As dependent variable, ROA only affected by company size; while MTBV was affected by company age.